Efficient recovery and sequencing of mutant genes from mammalian chromosomal DNA. - Ashman, C R (1986)
A retroviral shuttle vector was constructed by introducing the Escherichia coli xanthine (guanine) phosphoribosyltransferase gene (gpt) into the pZip-NeoSV(X)1 vector [Cepko, C. L., Roberts, B. E. & Mulligan, R. C. (1984) Cell 37, 1053-1062]. This vector was packaged into infectious virus which then was used to infect a hypoxanthine (guanine) phosphoribosyltransferase-deficient mouse cell line. Cell lines that expressed the gpt gene were isolated, and it was found that these cells contained a single integrated copy of the vector in a proviral form. Treatment of these cell lines with either ethyl methanesulfonate or BrdUrd produced a greater than 10-fold increase in the frequency of 6-thioguanine-resistant (Sgur) mutants. Intact gpt genes have been recovered from a number of Sgur cell lines after COS cell fusion and introduced into E. coli as part of a plasmid. The complete DNA sequences of three mutant genes have been determined. Two of the mutant genes have a single base substitution, whereas the third has a 34-base-pair deletion. This system should be valuable for analyzing mutagenic specificity and the molecular mechanisms of chemical mutagenesis in mammalian cells. A potentially important feature of the system relative to other shuttle-vector systems is that the mutations are induced in genes integrated into mammalian chromosomes rather than in genes existing as part of autonomously replicating plasmids.